Digital Transformation in Rural Communities: Enhancing Village Governance and Citizen Participation - Yar, Fayaz Mazloum (Politeknik Siber Cerdika Internasional, 2024)
Digital transformation has become a driving force in reshaping village governance and citizen participation in rural communities. This study aims to analyze the impact of digitalization on village governance and the role of digital tools in enhancing citizen engagement in rural areas. Using a qualitative approach, the study gathered data through interviews and focus group discussions with local stakeholders, including villagers and village officials, to gain in-depth insights. The findings indicate that digital tools improve operational efficiency in village governance and create opportunities for broader citizen participation. However, challenges such as limited internet access and low digital literacy hinder the optimal implementation of digital transformation. The study recommends improvements in digital infrastructure and digital literacy programs focusing on engaging all age groups. These findings guide policymakers in formulating more inclusive digitalization strategies for rural communities.